Pharmacological properties of selenium and its preparations: from antioxidant to neuroprotector - Belenichev, I. F.; Gorchakov, N. O.; Samura, I. B.; Savchenko, N. V.; Bukhtiyarova, N. V.; Popazova, O. O.; Бєленічев, Ігор Федорович; Самура, Ірина Борисівна; Бухтіярова, Ніна Вікторівна; Попазова, Олена Олександрівна (My University, 2021)
Selenium is an essential component of more than two dozen enzymes and other selenoproteins that play critical roles in reproduction, DNA synthesis, thyroid hormone metabolism, and protection from oxidative damage and infection. Selenium has a protective action against some forms of cancer and cardiovascular diseases, modulates levels of inflammatory mediators, promotes to maintain bone homeostasis and protects against bone loss. Selenium significance as a cardioprotective agent may be associated not only with its antioxidant properties, but also with its ability to prevent inflammation, autophagy, as well as the intrinsic and extrinsic apoptosis pathways. Signaling pathways, such as p-AMPK, PARP, Nrf2, STAT, are involved in the protective effects of selenium. Selenium protects against cardiovascular damage by increasing the survival rate of cardiomyocytes, including a mitochondria-dependent pathway and autophagy through peroxisome proliferator-activated receptors. Research demonstrating neuroprotective and cardioprotective effects of selenium preparations – selenoline, selenocysteine and selenomethionine – is growing at a rapid rate. It has been established that these compounds are able to normalize the levels of heat shock proteins (HSP70), which limit the cytotoxic effects of free radicals, produce energotropic action, prevent a decrease in the membrane mitochondria charge, and the opening of the mitochondrial pore. Also regulate the expression of transmembrane factors NF-kB, c-fos, which is associated with their main biological function of chaperone proteins, providing protection of neurons from damage. In this review, we want to emphasize pharmacological role of Selenium and its derivatives on human health is very complex and has yet to be fully understood.
Keywords: selenium; heat shock proteins; cardioprotective; neuroprotective; antioxidant action